2015
DOI: 10.16916/aded.62200
|View full text |Cite
|
Sign up to set email alerts
|

TEOG Sınavı Sorularının Okuma Becerisiyle Çözülebilme Düzeyi

Abstract: ÖzOkuma, bilgi edinmenin en etkili yollarından biri olarak eğitim-öğretimde sıkça kullanılan becerilerdendir. Her ne kadar bütün derslerin temeli okuduğunu anlamaya dayansa da esas olan, derslerin kendi disiplin alanına ait kazanımlardır. Dolayısıyla farklı derslere yönelik ölçme ve değerlendirme süreçlerinde, derse ait kazanımlar temel alınmalıdır. 2013-2014 eğitim öğretim yılından bu tarafa 8. sınıflarda uygulanan TEOG sınavları da kazanım temelli bir ölçme ve değerlendirmeyi amaçlamaktadır. Bu çalışmada, TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
1
2
0
3
Order By: Relevance
“…The results of this research support the results of many studies (Durukan, 2011;Ceran and Deniz, 2015;Karadağ, 2012;Arı and Keskin, 2016;Arı, 2017).…”
Section: Extended Abstract Introductionsupporting
confidence: 91%
“…The results of this research support the results of many studies (Durukan, 2011;Ceran and Deniz, 2015;Karadağ, 2012;Arı and Keskin, 2016;Arı, 2017).…”
Section: Extended Abstract Introductionsupporting
confidence: 91%
“…However, in the results of many studies examining the relationship between reading and writing skills and academic achievement, it is stated that literacy skills are the most important variable that predict academic achievement (Cox, Friesner and Khayum, 2003;van Kleeck, 2008;Whitten, Labby and Sullivan, 2019). In the study conducted by Ceran and Deniz (2015), it was determined that in the Transition from Basic Education to Secondary Education (TEOG) exam, the reading outcomes were effective in answering the questions of the lessons other than the mathematics lesson, and most of the questions could be solved only by reading comprehension and vocabulary without the need for knowledge and acquisitions of the course has been. This result shows that reading and writing skills are in a position that highlights success not only in Turkish lessons but also in all academic fields.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Okuma ve yazma becerileri ile akademik başarı arasındaki ilişkiyi inceleyen pek çok araştırmanın sonuçlarında okuma yazma becerilerinin akademik başarıyı yordayan en önemli değişken olduğu belirtilmektedir (Cox, Friesner ve Khayum, 2003;van Kleeck, 2008;Whitten, Labby ve Sullivan, 2019). Diğer taraftan, ortaokul düzeyinde dahi olsa, okuma ve yazma becerileri açısından güçlük yaşayan bireylerin akademik başarılarının daha düşük olduğu görülmektedir (Bayat, Şekercioğlu ve Bakır, 2014;Ceran ve Deniz, 2015;Erdem, 2016;Göktaş, 2010;Serbin, Stack ve Kingdon, 2013). Bu sonuçlar, öğrencilerin ilkokulda okuma ve yazma becerileri açısından karşılaştıkları güçlüklerin ilerdeki akademik başarılarını da etkileyen bir konumda olduğunu göstermektedir.…”
Section: Conclusion and Discussionunclassified
See 1 more Smart Citation
“…In this respect, it can be said that Turkish language lesson is the basis of other lessons and individuals who are not competent in their mother tongue will have difficulty in other lessons (Guneyli, 2007). Therefore, there is a significant relationship between Turkish language lesson (mother tongue lesson) and other lessons (Bloom 1995;Ural & Ulper, 2013;Bayat, Sekercioglu & Bakir, 2014;Sever, 2011;Ceran & Deniz, 2015). In studies on this subject, although emphasis has been placed on education councils and curriculums prepared to date, it is observed that the students do not show sufficient success in national and international exams (Acar, 2012;Akbaba-Altun, 2009;Bozkurt, 2016).…”
Section: Introductionmentioning
confidence: 99%